Se sentir capable de rester dans son emploi jusqu’à la retraite ? - Anne-Françoise Molinié (Perspectives Interdisciplinaires sur le Travail et la Santé)
What occupational and health factors make employees feel - or not - that they are capable of remaining in their jobs until retirement? According to the French survey VISAT, the proportion of employees who say that they don’t feel capable is decreasing with age. It remains that at 52 years of age, it is still the case for 14% of women and 6% of men. The difficulty of current and past work (postural difficulty, carrying heavy loads, etc.) and a poor state of perceived health have a significant influence on this assessment. But the results stress the important role played by variables relating to the meaning of work (such as work allows yo uto learn or having the means to do quality work).Five years later, employees 52 years of age who had answered in 1996 that they do not feel capable of remaining in their job until retirement have (everything being equal) a higher probability of not being employed either due to retirement or pre-retirement, or due to unemployment or inability; at 32 or 42 years of age, they have a higher probability of having changed jobs or being unemployed.